Evaluasi Penerapan dan Dampak Program Badan Usaha Milik Desa (BUMDES) Terhadap Kesejahteraan Masyarakat Rumah Tangga Miskin (RTM) di Desa Babadan Kecamatan Karangrejo Kabupaten Tulungagung (Periode Mei 2014–April 2015) - Dendhi Agung Nugroho (Jurnal Ekonomi dan Studi Pembangunan, 2015)
The process of empowerment against poverty is a matter of humanity. The development of unbalanced cause social inequality, economic and political, both between countries, between regions, and between communities. Solving the problem of poverty should be based on a sound understanding of poor people themselves and their respect, protection and fulfillment of their basic rights.. With the guidance of Community Empowerment Board and Village Government (BPM-PD) Tulungagung, then on Monday, May 5th, 2014 formed village-owned enterprises (BUMDES) "WAHANA LESTARI". Subjects in this study were people who entered the category of Poor Households (RTM) in the village of Babadan as the main target of BUMDes also help some board of BUMDes Babadan village as the party most understand BUMDes program. The results showed that the implementation of this program has successfully overcome the problems of rural communities Babadan about capital needs for the community, especially for poor households category at least during the last year of the period May 2014 until 2015 April with business units are considered very helpful community of the need of capital to rural economies and societies can be lifted gradually.Keywords: BUMDes, Community Financial Institutions, poor households (RTM).